UPDATE ENDOMETRIOSIS - Pacheco Romero, José (2015)
Endometriosis is ectopic endometrial tissue implants, with effects on the peritoneal fluid, the number and the activity of macrophages, LH peaks, among others. It is considered that the incidence varies between 10 and 15% and in infertile women, 30 to 40%. We have found 48 cases of endometriosis in 79 laparoscopies, with an incidence of 60.7% 1. However, already in 1977 Williams and Pratt Mayo Clinic had found in 50% of gynecological laparotomy they performed. In the same institution, the pathologist Dockerty taught us to see, in each section than practiced, the deciduosis present in virtually all reviewed ovary, reconfirmed by my practice and recently in the literatura2 finding. Furthermore, it was observed that the cause of endometriosis is higher number of abortions and stillbirths ectopic pregnancies.